Factors associated with caries: a survey of students from southern Brazil - Tássia Silvana Borges; Natalí Lippert Schwanke; Cézane Priscila Reuter; Léo Kraether Neto; Miria Suzana Burgos
Abstract Objective: To describe the factors associated with dental caries among students from Santa Cruz do Sul, Rio Grande do Sul, Brazil. Methods: A cross-sectional study was conducted in a random sample of 623 students of both genders, aged 10-17 years old. Tooth decay was performed using the index of the World Health Organization (1997), DMFT (permanent dentition) that expresses the sum of decayed, missing and filled teeth per person. The maternal educational level was rated using criteria of the Brazilian Association of Market Research Companies. The remaining variables were obtained by a structured questionnaire. Poisson regression analysis was used to test the association between variables using robust models and a subsequently adjusted model. Data were expressed as prevalence ratio (PR). Results: Multivariate analysis identified the following factors related to the experience of dental caries: residence in rural municipalities (PR: 1.15; 95%CI: 1.0-1.3), attending a city school (PR: 3.30; 95%CI: 1.1-9.4) or a state school (PR: 3.40; 95%CI: 1.1-9.6); and having an illiterate mother or a mother that only attended up to the 4th year of school (PR: 1.67; 95%CI: 1.1-2.4) or high school (PR: 1.54; 95%CI: 1.1-2.2). Conclusions: The presence of caries in students in southern Brazil was associated with residence in rural areas, mother with little education and attendance to a public school.